Numerical Simulation of Sediment Transport along a Channel with Underwater Sill. (2017) - Azizah, Nurul; Triatmadja, Radianta; Kironoto, Bambang Agus
Abstract: Sediment prevention structures such as underwater sill (UWS) may be used to divert the sediment movement, and prevent it to enter the port basin or navigation channel. In this study, a quasi 3D-numerical model called multilayered model based on the Method of Characteristics was utilized to simulate the flow, and a particle tracking method was developed to simulate the sediment transport around an UWS. A straight channel with an UWS approximately a half way between upstream and downstream boundaries was simulated. The height of the UWS was varied to observe the effectiveness of such structure against sedimentation. The influence of UWS on flow and sedimentation pattern, vertical distribution of suspended sediment concentration, and the implication of effectiveness of underwater sill structures to control the flow and reduce sedimentation were analyzed. The numerical simulations indicated that the UWS significantly altered the flow/current pattern. It presence contributes in reducing the sediment transport that cause siltation problem in port basin.